Effect of microstructural evolution on mechanical and electrical properties of Ag–Mo thin films. (2nd September 2021) - Gao, Baolong; Zhou, Lingping; Zhang, Chao; Zhu, Jiajun; Fu, Licai; Yang, Wulin; Li, Deyi
ABSTRACT: Herein, Ag–Mo films were deposited on Si(100) substrates by magnetron co-sputtering. The phase evolution and microstructural investigation revealed that the pure Ag phase and no Ag(Mo) solid solution were formed in the Ag-rich films even though the Mo content reached 53 at.%. However, the metastable Mo(Ag) solid solution was formed on the Mo-rich side. The Young's modulus, hardness, resistivity and the relationship between these properties and the microstructural evolution of Ag–Mo films were studied. Precisely, when the Mo content was controlled at 86 at.%, the hardness reached the maximum value of 14.64 GPa, and exceeded that of the pure Mo film. Meanwhile, the resistivity appeared to be a minimum value because the film had the maximum solid solubility and better crystallinity. The study on the microstructural, mechanical and electrical properties of Ag–Mo films provided a basis for the application of the film in electrical contact coatings.